The comparision of localization features of hypertext editors - Laucius, Rimgaudas (Lietuvos matematikos rinkinys, 2003)
There are results of investigation accomplished in comparison of freely distributed hypertext editors localization problems presented in this paper. The aims of this investigation are: to evaluate freely distributed hypertext editors internationalization level, find out their localization problems and their causes.